2011
DOI: 10.7763/ijbbb.2011.v1.9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Epinephelus fuscoguttatus and Epinephelus hexagonatus Inferred from Mitochondrial Cytochrome b Gene Sequences using Bioinformatic Tools

Abstract: Abstract-Molecular markers can be identified via a DNA test regardless of the developmental stage, age, or environmental challenges experienced by the organism. The degree of conservation of sequence using the cytochrome b gene from mitochondrial DNA is sufficient to discriminate between closely related species. A partial DNA sequence of cytochrome b gene was used to investigate the molecular relationship between Epinephelus hexagonatus and Epinephelus fuscoguttatus. Polymerase Chain Reaction (PCR) and sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…The samples from Terengganu were clustered on the right side of the plot, and the samples from Sabah (Borneo) were clustered on the left, which indicates that the ATR-FTIR is able to separate samples based on location. The separation of individuals in the score scatter plot was in agreement with known locations of the fish and also supports the findings of a previous study [ 10 ]. However, the score scatter plot could not separate E. fuscoguttatus from E. hexagonatus , indicating that the samples should be in one group.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The samples from Terengganu were clustered on the right side of the plot, and the samples from Sabah (Borneo) were clustered on the left, which indicates that the ATR-FTIR is able to separate samples based on location. The separation of individuals in the score scatter plot was in agreement with known locations of the fish and also supports the findings of a previous study [ 10 ]. However, the score scatter plot could not separate E. fuscoguttatus from E. hexagonatus , indicating that the samples should be in one group.…”
Section: Resultssupporting
confidence: 91%
“…Phylogenetic inference by neighbor-joining and maximum-parsimony analysis revealed that E. fuscoguttatus and E. hexagonatus representing a similar taxon analysed either in COI, COIII or in 16S. This study also supported our previous phylogenetic relationships of E. fuscoguttatus and E. hexagonatus using cytochrome b mtDNA markers [ 10 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is because cytochrome b, contain slowly evolving sites which facilitate the investigation of species identification and their relationships [18]. Also, the cytochrome b markers are useful in aquaculture [8,18], evolutionary biology, genetic conservation, population genetics, molecular ecology and food safety [19,20,21]. Some of the important fish species studied by Cyt.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular procedures have been applied in many studies for new species identification and it is clear that these methods have great potential in resolving identification and phylogenic relationship of cryptic species and could be highly effective in classification of confusing species (Teletchea, 2009). Cytochrome b gene (Cytb) is frequently utilized for fish identification and phylogenetic study (Song et al, 1998;Biswas et al, 2001;Farias et al, 2001;Perkins & Schall, 2002;Perdices et al, 2004;Baharum & Nurdalila, 2011).…”
Section: Introductionmentioning
confidence: 99%